Protocol for a new family history of addiction density score to aid in the treatment of alcohol and substance use disorders - Jessica L. Bourdon; Jordan Wright; Sabrina Verdecanna; Mer W. Francis; Vivia V. McCutcheon (Drug and Alcohol Dependence Reports)
Background: While molecular and non-molecular genetic testing are the gold standard for assessing a person’s familial liability for substance use disorders, such testing is often inaccessible. Family history information collected at intake is an alternative, but tools to effectively utilize this information are excessively complex. The aims of the study are threefold: 1) Describe a protocol for the collection of family history in a thorough and straightforward manner. 2) Provide an algorithm to convert family history information to numerical scores. 3) Present the aggregated results from the pilot testing of the protocol. Methods: All patients (N = 871) underwent a comprehensive assessment that included the family history protocol. Descriptive statistics, t-tests and Pearson Correlation were used to analyze the scores and determine key differences by demographic categories (sex/race/ethnicity/substance/age). Results: The protocol asked patients four key questions about 1st and 2nd degree relatives while completing a family pedigree. Answers were transferred into an algorithm to output a score for each patient. This score took affectedness and relatedness of each family member into account. The average number of affected relatives was 5.24 (SD=3.17), and there were significant sex, race, and primary substance score differences. Conclusions: This study provides the addiction field with a novel, freely available, and easily implementable family history protocol that has several potential clinical applications. While more research is needed, pilot results provide a valuable research tool, insight into a typical family history for those at an inpatient addiction treatment center, and steps toward closing the research-to-practice gap in this field.